Soil Test based Fertilizer Recommendation under IPNS for Pearl millet in Torripsamments of Rajasthan - Gulati, I J; Yadav, S R; Singh, S P; Singh, R; Meena, B S (Annals of Arid Zone, 2016)
Soil test crop response correlation studies were conducted with pearl millet (var. HHB-67) under integrated plant nutrition system (STCR-IPNS) in Torripsamments soils of Rajasthan during kharif 2002. Fertilizer adjustment equations under IPNS were formulated for pearl millet following Ramamoorthy’s inductive-cum targeted yield model. The nutrient requirement for producing 100 kg of pearl millet was found to be 2.12, 1.51 and 3.19 kg of N, P2O5 and K2O, respectively. The per cent nutrient utilization efficiencies from soil and fertilizer nutrients were found to be 31.83 and 18.06 for N, 60.83 and 20.35 for P2O5 and 79.52 and 40.78 for K2O, respectively. Likewise the per cent nutrient utilization efficiency from farm yard manure (FYM) was 34.57 for N, 21.74 for P2O5 and 137.10 for K2O, respectively. In STCR-IPNS technology, the fertilizer doses are tailored to the requirements of specific yield targets of pearl millet taking into account the contribution from soil, fertilizers and organics.